Effect of thin intermediate-layer of InAs quantum dots on the physical properties of InSb films grown on (001) GaAs - Lim, Ju Young; Song, Jin Dong; Yang, Hae Suk (ELSEVIER SCIENCE SA, 2012)
In this study the formation of a semiconducting InSb layer, preceded by the growth of an intermediate layer of InAs quantum dots, is attempted on (001) GaAs substrate. From the analysis of atomic-force-microscopy and transmission-electron-microscopy images together with Raman spectra of the InSb films, it is found that there exists a particular layer-thickness of similar to 0.5 mu m above which the structural and transport qualities of the film are considerably enhanced. The resultant 2.60-mu m-thick InSb layer, grown at the substrate temperature of 400 degrees C and under the Sb flux of 1.5x10(-6) Torr, shows the electron mobility as high as 67,890 cm(2)/Vs. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: MOLECULAR-BEAM EPITAXY; HIGH-QUALITY INSB; SUBSTRATE; MAGNETORESISTANCE; PHOTODETECTORS; SEMICONDUCTORS; SENSORS